Price Negotiation of E-Purchasing Catalog In Government Procurement of Goods/Services - Ahmaddien, Iskandar (ARKA INSTITUTE, 2023)
The role of the purchasing manager (purchase manager/commitment manager) in price negotiations is very important because the price of the items listed in the catalog is the price set by the catalog supplier. The government details and strictly regulates electronic shopping lists in price negotiations. However, in practice, this is difficult to apply because information about the strategy and ethics of purchasing managers of goods/services in price negotiations is limited, so that the procedures for implementing strategies and ethics in price negotiations for online shopping must be developed. This study is intended as a practical academic approach for procurement organizers to negotiate the price of an electronic purchase list, starting from procurement preparation and implementation of an electronic purchase list in the LKPP online purchase list application. This study uses a qualitative descriptive method by looking at various government regulations regarding the procurement of goods/services and other supporting literature. The result of this study is PP/PPK in negotiating prices for e-Purchasing Catalogs has been given technical guidance by LKPP through Decree of the Head of LKPP Number 122 of 2022 concerning Procedures for Organizing Electronic Catalogs